2009
DOI: 10.1177/1077727x08329561
|View full text |Cite
|
Sign up to set email alerts
|

The Family and Consumer Sciences Body of Knowledge and the Cultural Kaleidoscope: Research Opportunities and Challenges

Abstract: As a profession established during the Progressive Era when industrialization, immigration, urbanization, and other social forces were prevalent, family and consumer sciences is once again faced with similar social, economic, and technological societal conditions. This article addresses how family and consumer sciences, through its body of knowledge, is positioned to address the social changes of the 21st century. In particular, the article examines the family and consumer sciences body of knowledge in light o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 56 publications
(63 reference statements)
0
36
0
1
Order By: Relevance
“…Nickols et al. () identified the need for family and consumer sciences researchers and practitioners to apply the family and consumer sciences body of knowledge to strengthen theory development, to address changes, and using the body of knowledge to frame both immediate and perennial problems. It is apparent that graduate students’ graduate research is evolving within this structure, specifically addressing change and immediate and perennial problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nickols et al. () identified the need for family and consumer sciences researchers and practitioners to apply the family and consumer sciences body of knowledge to strengthen theory development, to address changes, and using the body of knowledge to frame both immediate and perennial problems. It is apparent that graduate students’ graduate research is evolving within this structure, specifically addressing change and immediate and perennial problems.…”
Section: Discussionmentioning
confidence: 99%
“…This review of graduate student research in family and consumer sciences shows that graduate students and their advisors are seeking answers to problems facing individuals, families, and communities with the goal of improving daily life. Nickols et al (2009) identified the need for family and consumer sciences researchers and practitioners to apply the family and consumer sciences body of knowledge to strengthen theory development, to address changes, and using the body of knowledge to frame both immediate and perennial problems. It is apparent that graduate students' graduate research is evolving within this structure, specifically addressing change and immediate and perennial problems.…”
Section: Discussionmentioning
confidence: 99%
“…Started as the American Home Economics Association (AHEA) in 1909, AAFCS prepares professionals for "careers focused on people and their environment" (AAFCS, Who We Are, n.d.), and it has developed a comprehensive body of knowledge to help families and consumers make informed decisions for their well-being and quality of life (Nickols et al, 2009). Started as the American Home Economics Association (AHEA) in 1909, AAFCS prepares professionals for "careers focused on people and their environment" (AAFCS, Who We Are, n.d.), and it has developed a comprehensive body of knowledge to help families and consumers make informed decisions for their well-being and quality of life (Nickols et al, 2009).…”
Section: Housing Research Organizations and Journals American Associamentioning
confidence: 99%
“…Housing has been an important area of study among the members of the AAFCS. Started as the American Home Economics Association (AHEA) in 1909, AAFCS prepares professionals for "careers focused on people and their environment" (AAFCS, Who We Are, n.d.), and it has developed a comprehensive body of knowledge to help families and consumers make informed decisions for their well-being and quality of life (Nickols et al, 2009). AAFCS covers a range of fields related to family and consumer sciences including disciplines such as housing, human development, and family studies, food science and nutrition, and textiles and apparel, and personal finance/ consumer economics.…”
Section: Housing Research Organizations and Journals American Associamentioning
confidence: 99%
“…Today's mission of family and consumer sciences continues to have a similar scope, utilizing an integrated approach to seeking greater understanding of the relationships between individuals, families, and communities and the micro and macro environments in which they live (Nickols et al., ). The family and consumer sciences body of knowledge focuses on investigating basic human needs with the core elements of individual well‐being, family strengths, and community vitality with a systems‐based approach to investigation and practice (Nickols et al., ). The research completed by family and consumer sciences graduate students in 2017 demonstrates not only the breadth and depth of the field, but also the interdisciplinary nature of the field's inquiry.…”
mentioning
confidence: 99%